2023
DOI: 10.1021/acs.jafc.3c01669
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Diverse Phenolic Amides from the Fruits of Lycium barbarum with Potent α-Glucosidase, Dipeptidyl Peptidase-4 Inhibitory, and PPAR-γ Agonistic Activities

Abstract: A total of nine new phenolic amides (1–9), including four pairs of enantiomeric mixtures (3–5 and 8), along with ten known analogues (10–19) were identified from the fruits of Lycium barbarum using bioassay-guided chromatographic fractionation. Their structures were elucidated by comprehensive spectroscopic and spectrometric analyses, chiral HPLC analyses, and quantum NMR, and electronic circular dichroism calculations. Compounds 5–7 are the first example of feruloyl tyramine dimers fused through a cyclobutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Compound 2 exhibited the characteristic signals of tetrahydrofuran (THF)-like lignans, manifested by the coupling constants of H-8/H-8′ (each dd, J = 9.0 and 7.8 Hz). 51,52 The placement of the methoxyl groups at C-3 and C-3′ was determined by their HMBC correlations (Figure 2). The correlations in the NOESY spectrum were observed between H-8 and (H-7′ and H-2), and H-8′ and (H-7 and H-2′) (Figure 3), indicating a 7,8-trans/8,8′-trans/7′,8′-trans relative configuration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 2 exhibited the characteristic signals of tetrahydrofuran (THF)-like lignans, manifested by the coupling constants of H-8/H-8′ (each dd, J = 9.0 and 7.8 Hz). 51,52 The placement of the methoxyl groups at C-3 and C-3′ was determined by their HMBC correlations (Figure 2). The correlations in the NOESY spectrum were observed between H-8 and (H-7′ and H-2), and H-8′ and (H-7 and H-2′) (Figure 3), indicating a 7,8-trans/8,8′-trans/7′,8′-trans relative configuration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, the long-range correlation between H-8″ and C-9, and H-8‴ and C-9′ suggested that the two tyramine fragments were connected to the two phenylpropanoid through the amino group. Compound 2 exhibited the characteristic signals of tetrahydrofuran (THF)-like lignans, manifested by the coupling constants of H-8/H-8′ (each dd, J = 9.0 and 7.8 Hz). , The placement of the methoxyl groups at C-3 and C-3′ was determined by their HMBC correlations (Figure ). The correlations in the NOESY spectrum were observed between H-8 and (H-7′ and H-2), and H-8′ and (H-7 and H-2′) (Figure ), indicating a 7,8-trans/8,8′-trans/7′,8′-trans relative configuration. The absolute configuration was further confirmed through the quantum chemical time-dependent density-functional theory (TDDFT) calculations of ECD.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, the number of articles incorporating the incorrectly elucidated structures is still limited. However, one article recently published in the Journal of Agricultural and Food Chemistry uses the incorrect structures for a docking study, which exemplifies why it is important to rectify the elucidation of these structures.…”
mentioning
confidence: 99%